A straightforward reductive approach for the deoxygenation, activation and functionalization of ultrashort single-walled carbon nanotubes - Bao, Lipiao; Martin, Oliver; Wei, Tao; Perez-Ojeda Rodriguez, Maria Eugenia; Hauke, Frank; Hirsch, Andreas (Carbon, 2021)
We report here a straightforward reductive approach for the deoxygenation, activation and functionalization of ultrashort single-walled carbon nanotubes (us-SWCNTs). Us-SWCNTs with lengths of only 20–50 nm were prepared by the low-temperature oxidative-cutting process which inevitably introduced oxygen-containing groups onto the nanotube framework. For the subsequent deoxygenation, six routes have been investigated and the reduction with potassium is the optimal one that can efficiently remove the oxidized groups and consequently recover the inherent structures and properties of us-SWCNTs. This reductive approach permits at the same time very efficient activation of the chemically inert nanotubes by generating the intermediate us-SWCNTn- carbanions. Subsequent quenching these negative charges on the nanotube backbone using electrophiles affords very efficient covalent binding of distinct building blocks as porphyrin, phenyl or hexyl moieties onto us-SWCNTs. Additionally, the Birch-type reductive approach was also performed to realize the first hydrogenation of us-SWCNTs by using water as proton source and lithium as reducing agent.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Activation; Carbon nanotube; Functionalization; High degree of functionalization; Reduction; Ultrashort carbon nanotube

Covalent 2D Patterning, Local Electronic Structure and Polarization Switching of Graphene at the Nanometer Level - Bao, Lipiao; Zhao, Baolin; Assebban, M'hamed; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2021)
A very facile and efficient protocol for the covalent patterning and properties tuning of graphene is reported. Highly reactive fluorine radicals were added to confined regions of graphene directed by laser writing on graphene coated with 1-fluoro-3,3-dimethylbenziodoxole. This process allows for the realization of exquisite patterns on graphene with resolutions down to 200 nm. The degree of functionalization, ranging from the unfunctionalized graphene to extremely high functionalized graphene, can be precisely tuned by controlling the laser irradiation time. Subsequent substitution of the initially patterned fluorine atoms afforded an unprecedented graphene nanostructure bearing thiophene groups. This substitution led to a complete switch of both the electronic structure and the polarization within the patterned graphene regions. This approach paves the way towards the precise modulation of the structure and properties of nanostructured graphene.
CRIS-Team Scopus Importer:2021-05-07
Keywords: covalent patterning; fluorination; graphene; polarization switch; substitution

Covalently Doped Graphene Superlattices: Spatially Resolved Supratopic- and Janus-Binding - Bao, Lipiao; Kohring, Malte; Weber, Heiko B.; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2020)
Rational design and fabrication of graphene nanoarchitectures with multifunctionality and multidimensionality remains quite a challenge. Here, we present a synthetic sequence, based on the combination of two advanced patterned-functionalization principles, namely, laser-writing and poly(methyl methacrylate) (PMMA)-assisted lithographic processes, leading to unprecedented covalently doped graphene superlattices. Spatially resolved supratopic- and Janus-binding were periodically weaved on the graphene sheet, leading to four different types of zones with distinct chemical doping and structural properties. Notably, this is also the first realization of patterned Janus graphene. The elaborate chemical doping with micrometer resolution is unequivocally evidenced by scanning Raman spectroscopy (SRS) and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS). The design of the pattern as well as the degree of chemical doping on both opposite sides of graphene can be easily manipulated, rendering exciting potential for graphene nanosystems.
CRIS-Team Scopus Importer:2020-09-25

Hierarchical Assembly and Sensing Activity of Patterned Graphene-Hamilton Receptor Nanostructures - Bao, Lipiao; Zhao, Baolin; Ali, Muhammad; Assebban, M'hamed; Yang, Bowen; Kohring, Malte; Ryndyk, Dmitry A.; Heine, Thomas; Weber, Heiko B.; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials Interfaces, 2022)

Hypervalent Iodine Compounds as Versatile Reagents for Extremely Efficient and Reversible Patterning of Graphene with Nanoscale Precision - Bao, Lipiao; Zhao, Baolin; Yang, Bowen; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
Rational patterning and tailoring of graphene relies on the disclosure of suitable reagents for structuring the target functionalities on the 2D-carbon network. Here, a series of hypervalent iodine compounds, namely, 1-chloro-1,2-benziodoxol-3(1H)-one, 1,3-dihydro-1-hydroxy-3,3-dimethyl-1,2-benziodoxole, and 3,3-dimethyl-1-(trifluoromethyl)-1,2-benziodoxole is reported to be extremely efficient for a diversified graphene patterning. The decomposition of these compounds generates highly reactive Cl, OH, and CF3 radicals exclusively in the irradiated areas, which subsequently attach onto the graphene leading to locally controlled chlorination, hydroxylation, and trifluoromethylation, respectively. This is the first realization of a patterned hydroxylation of graphene, and the degrees of functionalization of the patterned chlorination and trifluoromethylation are both unprecedented. The usage of these mild reagents here is reasonably facile compared to the reported methods using hazardous Cl-2 or ICl and allows for sophisticated pattern designs with nanoscale precision, promising for arbitrary nanomanipulation of graphene's properties like hydrophilicity and conductivity by the three distinct functionalities (Cl, OH, and CF3). Moreover, the attachment of functional entities to these highly functionalized graphene nanoarchitectures is fully reversible upon thermal annealing, enabling a full writing/storing/reading/erasing control over the chemical information stored within graphene. This work provides an exciting clue for target 2D functionalization and modulation of graphene by using suitable hypervalent iodine compounds.
CRIS-Team WoS Importer:2021-07-09

Laser-Triggered Bottom-Up Transcription of Chemical Information: Toward Patterned Graphene/MoS2 Heterostructures - Chen, Xin; Assebban, M'hamed; Kohring, Malte; Bao, Lipiao; Weber, Heiko B.; Knirsch, Kathrin; Hirsch, Andreas (Journal of the American Chemical Society, 2022)

Nanocarbons: Basics and Advanced Applications - Bao, Lipiao; Xie, Yun-Peng; Qie, Long (Frontiers in Chemistry, 2021)
CRIS-Team Scopus Importer:2021-04-09
Keywords: carbon fiber; fullerene; graphene; nanocarbons; water purification

Recent Advances in Graphene Patterning - Wei, Tao; Bao, Lipiao; Hauke, Frank; Hirsch, Andreas (ChemPlusChem, 2020)
As an emerging field of research, graphene patterning has received considerable attention because of its ability to tailor the structure of graphene and the respective properties, aiming at practical applications such as electronic devices, catalysts, and sensors. Recent efforts in this field have led to the development of a variety of different approaches to pattern graphene sheets, providing a multitude of graphene patterns with different shapes and sizes. These established patterning techniques in combination with graphene chemistry have paved the road towards highly attractive chemical patterning approaches, establishing a very promising and vigorously developing research topic. In this review, an overview of commonly used strategies is presented that are categorized into top-down and bottom-up routes for graphene patterning, focusing mainly on new advances. Other than the introduction of basic concepts of each method, the advantages/disadvantages are compared as well. In addition, for the first time, an overview of chemical patterning techniques is outlined. At the end, the challenges and future perspectives in the field are envisioned.
CRIS-Team Scopus Importer:2020-08-14
Keywords: covalent functionalization; graphene; lithography; nanostructures; patterning

Spatially Resolved Bottom-Side Fluorination of Graphene by Two-Dimensional Substrate Patterning - Bao, Lipiao; Zhao, Baolin; Lloret, Vicent; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2020)
Patterned functionalization can, on the one hand, open the band gap of graphene and, on the other hand, program demanding designs on graphene. The functionalization technique is essential for graphene-based nanoarchitectures. A new and highly efficient method was applied to obtain patterned functionalization on graphene by mild fluorination with spatially arranged AgF arrays on the structured substrate. Scanning Raman spectroscopy (SRS) and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS) were used to characterize the functionalized materials. For the first time, chemical patterning on the bottom side of graphene was realized. The chemical nature of the patterned functionalization was determined to be the ditopic scenario with fluorine atoms occupying the bottom side and moieties, such as oxygen-containing groups or hydrogen atoms, binding on the top side, which provides information about the mechanism of the fluorination process. Our strategy can be conceptually extended to pattern other functionalities by using other reactants. Bottom-side patterned functionalization enables utilization of the top side of a material, thereby opening up the possibilities for applications in graphene-based devices.
CRIS-Team Scopus Importer:2020-03-31
Keywords: ditopic functionalization; fluorination; graphene; substrate patterning

Synthesis and Photophysical Properties of a Sc3N@ C80‐Corrole Electron Donor–Acceptor Conjugate - Liu, Bin; Fang, Hongyun; Li, Xiaofang; Cai, Wenting; Bao, Lipiao; Rudolf, Marc; Plass, Fabian; Fan, Louzhen; Lu, Xing; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
Embedding endohdedral metallofullerenes (EMFs) into electron donor–acceptor systems is still a challenging task owing to their limited quantities and their still largely unexplored chemical properties. In this study, we have performed a 1,3-dipolar cycloaddition reaction of a corrole-based precursor with Sc3N@C80 to regioselectively form a [5,6]-adduct (1). The successful attachment of the corrole moiety was confirmed by mass spectrometry. In the electronic ground state, absorption spectra suggest sizeable electronic communications between the electron acceptor and the electron donor. Moreover, the addition pattern occurring at a [5,6]-bond junction is firmly proven by NMR spectroscopy and electrochemical investigations performed with 1. In the electronically excited state, which is probed in photophysical assays with 1, a fast electron-transfer yields the radical ion pair state consisting of the one-electron-reduced Sc3N@C80 and of the one-electron-oxidized corrole upon its exclusive photoexcitation. As such, our results shed new light on the practical work utilizing EMFs as building blocks in photovoltaics.<br
Keywords: corroles; donor–acceptor systems; fullerenes; metallocycles; photophysics